Emerging fungal infections among children: A review on its clinical manifestations, diagnosis, and prevention - Akansha Jain; Shubham Jain; Swati Rawat (Wolters Kluwer Medknow Publications, 2010)
The incidence of fungal infections is increasing at an alarming rate, presenting an enormous challenge to healthcare professionals. This increase is directly related to the growing population of immunocompromised individuals especially children resulting from changes in medical practice such as the use of intensive chemotherapy and immunosuppressive drugs. Although healthy children have strong natural immunity against fungal infections, then also fungal infection among children are increasing very fast. Virtually not all fungi are pathogenic and their infection is opportunistic. Fungi can occur in the form of yeast, mould, and dimorph. In children fungi can cause superficial infection, i.e., on skin, nails, and hair like oral thrush, candida diaper rash, tinea infections, etc., are various types of superficial fungal infections, subcutaneous fungal infection in tissues under the skin and lastly it causes systemic infection in deeper tissues. Most superficial and subcutaneous fungal infections are easily diagnosed and readily amenable to treatment. Opportunistic fungal infections are those that cause diseases exclusively in immunocompromised individuals, e.g., aspergillosis, zygomycosis, etc. Systemic infections can be life-threatening and are associated with high morbidity and mortality. Because diagnosis is difficult and the causative agent is often confirmed only at autopsy, the exact incidence of systemic infections is difficult to determine. The most frequently encountered pathogens are Candida albicans and Aspergillus spp. But other fungi such as non-albicans Candida spp. are increasingly important.